Prevalence and Risk Factors of Gastrointestinal Helminth Infection in Pet Cats in Wonogiri District, Central Java - Sekarsari, Dara Ayu Pramesti; Saputro, Amung Logam; Agustono, Bodhi; Yunita, Maya Nurwartanti; Praja, Ratih Novita; Solikhah, Tridiganita Intan (Universitas Airlangga, 2023)
Gastrointestinal helminth infection is the most common and the easiest infection to infect wild cats or pet cats but is often ignored by the cat owners because sometimes there are no symptoms or a lack of attention from the cat owner to their pet cat. The aim of this study was to estimate the prevalence and risk factors of gastrointestinal helminth infection in pet cats in Wonogiri District, Central Java. A total of 100 cat samples were evaluated using a questionnaire, then fecal microscopic examination using simple native method, sedimentation, and floatation methods. Data obtained from this study were presented descriptively and analyzed using the Chi-Square test. The result showed that 37 out of 100 fecal samples were found positive infected with gastrointestinal helminth including Toxocara cati and Dipylidium caninum or the prevalence of gastrointestinal helminth infection can be calculated at 37%. The result of the analysis of significant risk factors were breed, number of pet cat owners, grooming, deworming, and vaccination.